Desenvolvimento urbano da cidade do Rio de Janeiro: uma visão através da legislação reguladora da época, 1925/1975 - Oliveira, Ligia Gomes de (1978)
In the last fifty years the territo:ry which today forrns the basis for the Municipality of Rio de Janeiro was the object of two urban developrent plans, thirty five years apart from each other. None of them was adopted as an effective planning instrurrent. Now, a third plan is being prepared, under the name of Basic Urbanistic Plan. In these fifty years, many pieces of legislation were enacted on local zoning, and five codifications were approved referring to regulation of land utilization, to priority orientations for urban expansion, to conditions for building and constructing, etc. Meanwhile, the institutional status of that territory in the Brazilian Federation changed fran a Federal District (the national Capital), to that of a member state which recently became a Municipality, the center of a Metropolitan Region. Several agencies were established during the same period, and a few other were abolished (Di visions, Commissions, councils, Bureaus, Superintendencies), all of them hàving as their initial purpose the preparation and/or inplementation of plans and projects on local urban developrent. This dissertation aims at a brief analysis of the evolution of Urban Planning for the present Municipality of Rio de Janeiro. It will try to establish, whenever possible, the interrelations which should explain the developrent of the process focused on this dissertation.